Analysis Of The Influence Of Motivation And Work Discipline On Employee Performance At PT. Kostec Indonesia Mandiri At The Cilegon Branch Office - Ruri Caturina; Junaidi, Junaidi (Journal of Law, Social Science, and Management Review, 2025)
The object of the study at PT. Kostec Indonesia Mandiri at the Cilegon Branch Office This study aims to determine the effect of motivation and work discipline on the performance of PT. Kostec Indonesia Mandiri at the Cilegon Branch Office. This study uses a survey by distributing questionnaires in the form of statements with a level of respondent agreement using a Likert scale of 1 to 5 distributed to respondents with a sample of 25 people consisting of employees at PT. Kostec Indonesia Mandiri. Data analysis was carried out using multiple linear regression with the SPSS version 23 program. The results of the study indicate that motivation has a positive effect on the performance of PT employees. Kostec Indonesia Mandiri is evidenced by the R square correlation coefficient of motivation on employee performance determination on employee performance of 75.3% and based on data work discipline has a positive effect on employee performance as evidenced by R. square of 71.3%. Changes in employee performance variables (bound) can be explained by work motivation variables while changes in employee performance dependent variables can be explained by motivation and work discipline variables with simultaneous test results, motivation and work discipline have a positive and significant effect on employee performance with F test results. It can be concluded that the motivation variable (X1) and the work discipline variable (X2) together have a significant effect on employee performance at PT. Kostec Indonesia Mandiri significantly by 83.3% and the remaining 16.7% is caused by other factors that were not studied by researchers. Explained by other factors that were not studied in this study. These other factors include the work environment, competence, career development and others.